Sistem Kendali Berbasis Mikrokontroler Menggunakan Protokol MQTT pada Smarthome - Hudan Abdur Rochman; Rakhmadhany Primananda; Heru Nurwasito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Internet of things (IoT) can be utilized for controlling and monitoring at a particular place such as home, commonly called Smarthome. One of the protocols which is deemed appropriate for the implementation of IoT and the Smarthome is MQTT protocol that has publish/subscribe communication mechanism. In which it requires network protocols, also supporting devices such as a sensor DHT11 which will be used to read the temperature conditions in Smarthome, the LDR which is a sensor of light intensity, LED lights that will represent controlling devices in Smarthome and microcontroller which acts as an actuator. Microcontrollers used in this study is a microcontroller Wemos D1 R2 which has a module ESP8266 that supports the establishment of a wireless network. In this research, a simple prototype of Smarthome is built, where two pieces of LED lights will go on and or out based on the value of temperature and light sensor data, then controlled through the application of the control system. The application can also display temperature and light sensor data in graph form as a function of the monitoring control system. The test result showed the number of packets sent using protocol MQTT at a time affect the delta time, wherein the shorter the sending time the smaller the delta time value, and the integrity value of data which is sent and received through MQTT protocl is 100%.